Selected Outcomes of Social Exclusion - Madeja-Bień, Kamila; Gamian-Wilk, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The article provides an overview of knowledge on social exclusion. It presents the dominant theoretical models describing this phenomenon. The meaning and importance of the sense of belonging and social support from a group is discussed. The possible consequences of social exclusion are then presented, and particularly the negative outcomes are highlighted. Both empirical findings and real life examples showing the occurrence of two different responses to social exclusion: aggression and prosocial behavior are described. Finally, the directions of further research on the ostracism phenomenon are presented.